Robust Grape Detector Based on SVMs and HOG Features - Škrabánek, Pavel; Doležel, Petr (My University, 2017)
Detection of grapes in real-life images is a serious task solved by researchers dealing with precision viticulture. In the case of white wine varieties, grape detectors based on SVMs classifiers, in combination with a HOG descriptor, have proven to be very efficient. Simplified versions of the detectors seem to be the best solution for practical applications. They offer the best known performance vs. time-complexity ratio. As our research showed, a conversion of RGB images to grayscale format, which is implemented at an image pre-processing level, is ideal means for further improvement of performance of the detectors. In order to enhance the ratio, we explored relevance of the conversion in a context of a detector potential sensitivity to a rotation of berries. For this purpose, we proposed a modification of the conversion, and we designed an appropriate method for a tuning of such modified detectors. To evaluate the effect of the new parameter space on their performance, we developed a specialized visualization method. In order to provide accurate results, we formed new datasets both for tuning and evaluation of the detectors. Our effort resulted in a robust grape detector which is less sensitive to image distortion.
Robustní detektor hroznů založený na SVMs a HOG příznacích
Keywords: computer vision, image recognition, conversion to grayscale, HOG features, SVM classifier, agricultural machinery; počítačové vidění, rozpoznání obrazu, převod do stupnice šedi, HOG příznaky, SVM klasifikátor, zemědělská technika